2017
DOI: 10.17265/2328-2185/2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Location Attractiveness as a Major Factor in Museum Visitors’ Choice and Satisfaction

Abstract: This paper is intended to give a contribution to the debate on the functional relationship between the museum and the local territory; more specifically, the aim of this study is to understand the role of a museum location in attracting visitors and influencing their processes of choice and satisfaction. The study follows, in particular, a previous study conducted by Mariani and Mussini (2013) Data show that, for the majority of visitors, the exhibition had been located elsewhere, they would not have visited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Researchers define different factors and dimensions which together form experience and afterward affect satisfaction and behavioral intentions. Consumer experience consists of a lot of factors and may be frequently influenced by their involvement, later compiling overall satisfaction (Codignola & Mariani, 2017). Experience economy theory in depth describes the experience as a model of four dimensions which are used widely in research: entertainment – the desire to joy; education – the desire to learn; esthetic – the desire to be in a certain place; and escapism – the desire to go and do something (Pine & Gilmore, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers define different factors and dimensions which together form experience and afterward affect satisfaction and behavioral intentions. Consumer experience consists of a lot of factors and may be frequently influenced by their involvement, later compiling overall satisfaction (Codignola & Mariani, 2017). Experience economy theory in depth describes the experience as a model of four dimensions which are used widely in research: entertainment – the desire to joy; education – the desire to learn; esthetic – the desire to be in a certain place; and escapism – the desire to go and do something (Pine & Gilmore, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have reported that satisfaction is connected to intention and represents a strong predictor of visitor revisit intention (Choo et al , 2016). Several authors have argued that the satisfaction of museum visitors represent a good foundation for increasing customer behavioural intention (Codignola and Mariani, 2017; Endah et al , 2017; Tofighian, 2015; Kang et al , 2018). However, limitations reveal that researchers have mostly ignored the impact of satisfaction on museums in the context of an event, as well as how events influence museum visitor behaviour.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Researchers have underlined the value of the experience for museum visitors (Roppola, 2012; Dirsehan, 2012) and events visitors (Rodriguez-Campo et al , 2019). Events create a certain experience that encompasses museums participating in these events; in addition, museums can create a very new experience during an event (Codignola and Mariani, 2017). It is reasonable to expect that experience is an important dimension of perceived value that it has an influence on a visitors' affective components and has an indirect influence on conative component (on their intention to revisit).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Cities begun attractive for students when they are already tourist destinations offering lot of events and activities. Due to their presence in a specific destination (Codignola & Mariani, 2017), museums and art exhibitions are few of the main attractions that benefit of the presence of language students as the visit is part of the 'full immersion' in the culture of the location offered by the schools.…”
Section: The Local Agenciesmentioning
confidence: 99%